Chelovek i zakon . Chelovek i zakon . People and the Law . Человек и закон - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Problem faced by homeless people; pornography and sexual violence; female crime; the professional and ethical standards of the police. Contributors: Karpov, Aleksandr (Anchor) Series description: Socio-political program. Broadcasted since 1974. The program is dedicated to the most important juridical, political, economic, and social issues. The program shows the work of the law enforcement authorities, and does investigative reporting. Проблема бездомных людей; порнография и сексуальное насилие; женская преступность; профессиональные и этические качества милиционеров. Создатели: Карпов, Александр (Ведущий/Ведущая) Описание серии: Общественно-политическая программа. Выходит с 1974 года. Основная тематика программы — важнейшие события в политической, экономической и социальной жизни страны. Выпуски освещают деятельность правоохранительных органов, включают журналистские расследования и разоблачения.